HIV seroconcordance among heterosexual couples in rural KwaZulu-Natal, South Africa: a population-based analysis - Kim, Hae-Young; Vandormael, Alain; Bärnighausen, Till (Journal of the International AIDS Society, 2020)
Introduction High levels of HIV seroconcordance at the population level reduce the potential for effective HIV transmission. However, the level of HIV seroconcordance is largely unknown among heterosexual couples in sub-Saharan Africa. We aimed to quantify the population level HIV seroconcordance in stable heterosexual couples in rural South Africa. Methods We followed adults (≥15 years old) using a population-based, longitudinal and open surveillance system in KwaZulu-Natal, South Africa, from 2003 to 2016. Sexual partnerships and HIV status were confirmed via household surveys and annual HIV surveillance. We calculated the proportions of HIV seroconcordance and serodiscordance in stable sexual partnerships and compared them to the expected proportions under the assumption of random mixing using individual-based microsimulation models. Among unpartnered individuals, we estimated the incidence rates and hazard of sexual partnership formation with HIV-positive or HIV-negative partners by participants' own time-varying HIV status. Competing risks survival regressions were fitted adjusting for sociodemographic and clinical factors. We also calculated Newman's assortativity coefficients. Results A total of 18,341 HIV-negative and 11,361 HIV-positive individuals contributed 154,469 person-years (PY) of follow-up. Overall, 28% of the participants were in stable sexual partnerships. Of the 677 newly formed stable sexual partnerships, 7.7% (95% CI: 5.8 to 10.0) were HIV-positive seroconcordant (i.e. both individuals in the partnership were HIV-positive), which was three times higher than the expected proportion (2.3%) in microsimulation models based on random mixing. The incidence rates of sexual partnership formation were 0.54/1000PY with HIV-positive, 1.12/1000PY with HIV-negative and 2.65/1000PY with unknown serostatus partners. HIV-positive individuals had 2.39 (95% CI: 1.43 to 3.99) times higher hazard of forming a sexual partnership with an HIV-positive partner than did HIV-negative individuals after adjusting for age, opposite-sex HIV prevalence (by 5-years age groups), HIV prevalence in the surrounding community, ART coverage and other sociodemographic factors. Similarly, forming a sexual partnership with an HIV-negative partner was 1.47 (95% CI: 1.01 to 2.14) times higher in HIV-negative individuals in the adjusted model. Newman's coefficient also showed that assortativity by participant and partner HIV status was moderate (r = 0.35). Conclusions A high degree of population level HIV seroconcordance (both positive and negative) was observed at the time of forming new sexual partnerships. Understanding factors driving these patterns may help the development of strategies to bring the HIV epidemic under control.